Analisis Sistem Pengelolaan Wakaf Tunai oleh Yayasan Citra Prakarsa Nusantara dan Dampaknya pada Tingkat Penerimaan Wakaf Tunai - Hanif, Ibrahim; Hamdani, Ikhwan; Sutisna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explain the cash waqf management system by Citra Prakarsa Nusantara Foundation and its impact on cash waqf receipts. The research methodolgy employed is qualitative, utilizing data collection techniques such as interviews, observations, and documentation. The data sources for this research include the daily management head of CPN and the media head of CPN. The research findings describe the cash waqf management system by CPN that targets waqifs from abroad, providing significant amounts of cash waqf. Additionally, CPN’s cash waqf management demonstrates adequate attention to communication with waqifs, thereby enhancing trust and credibility in the foundation. Although it targets cash waqifs from abroad, the land used to build cash waqf assets originates from waqifs in Indonesia. Through this management system, CPN achieves a high level of cash waqf receipts despite the risks that need to be anticipated. Furthermore, Citra Prakarsa Nusantara Foundation has several opportunities for development that should be considered. Keywords: Cash Waqf Management, Cash Waqf Receipts, Cash Waqf.